Frame Research in the Modern World and Domestic Linguistics - Nurzhaubek, А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2018)
At present, everyone knows the study of language from the point of view of cognition. The scientific works of researchers published in recent years contain important theoretical positions on the question of how our knowledge of the world is perceived, processed and stored, as they are structured in the language in the process of communication. Therefore, the frame is the most important object of study in linguistics. Frames are mental entities that have a name in the language and reflect a person’s cultural and national view of the world. The term frame has widely been used in the fields of interdisciplinary concepts for half a century and currently plays an important role in solving problematic issues that have not been solved in such areas as computer science, computer engineering, artificial intelligence, journalism, translation, foreign languages teaching, literary criticism and linguistics. Frames have many properties that make it possible to widely use them both for theoretical and practical purposes. Although the history of linguistics theory of the frame already began a long time ago, its scientific and logical concept is not systematically considered and scientifically not fully completed. In the meantime, we systematized and generalized definitions of the frame based on scientific works written around the world and in Kazakhstan.